Large-scale parallel discrete element simulations of granular flow - Walther, Jens H.; Sbalzarini, Ivo F. (Engineering computations, 2009)
Purpose - The purpose of this paper is to present large-scale parallel direct numerical simulations of granular flow, using a novel, portable software program for discrete element method (DEM) simulations.Design methodology approach - Since particle methods provide a unifying framework for both discrete and continuous systems, the program is based on the parallel particle mesh (PPM) library, which has already been demonstrated to provide transparent parallelization and state-of-the-art parallel efficiency using particle methods for continuous systems.Findings - By adapting PPM to discrete systems, results are reported from three-dimensional simulations of a sand avalanche down an inclined plane.Originality value - The paper demonstrates the parallel performance and scalability of the new simulation program using up to 122 million particles on 192 processors, employing adaptive domain decomposition and load balancing techniques.